Student 2 solved the equation correctly.
Student 1 incorrectly solved for a by subtracting x from both sides of the equation, which is not a valid step. This creates a=x-by, not a=yb-x.
Student 3 incorrectly solved for a by subtracting x from both sides of the equation and then multiplying by -1, which is not a valid step. This creates -by+x=a, not a=yb-x.
Student 2 correctly solved the equation by multiplying both sides by -1 to isolate a. This results in -yb+x=a, which is the correct solution.
Students were asked to solve the equation y=x−ab for a. Their work is shown below.
Student 1:
y=x−ab
by=x−a
by−x=a
Student 2:
y=x−ab
yb=x−a
yb−x=−a
−yb+x=a
Student 3:
y=x−ab
by=x−a
by−x=−a
−by+x=a
Which student solved the equation correctly? Justify your answer by explaining why the other two students solved the equation incorrectly.
1 answer